Electrochemical device and electronic device

By applying a first coating composed of lithium supplementary material and water-soluble polymer metal salt on the positive electrode of the lithium-ion battery, the problem of short circuit in the lithium-ion battery during the nailing process is solved, and higher capacity, volumetric energy density and nailing safety performance are achieved.

CN119833556AActive Publication Date: 2025-04-15NINGDE AMPEREX TECHNOLOGY LTD

Patent Information

Application Number
CN202510033880.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to internal short circuits during nailing, resulting in insufficient safety performance. It is difficult for the prior art to take into account the safety performance, capacity and volume energy density of nailing.

Method used

An electrochemical device is adopted, and the positive electrode sheet includes a positive electrode current collector, a first coating and a positive electrode material layer. The first coating is composed of lithium supplement material and water-soluble polymer metal salt. The lithium supplement material includes lithium iron phosphate, etc. Through infrared spectral characteristic peaks and strong hydrogen bonding, cohesion and adhesion are enhanced, and the safety performance of nail penetration is improved.

Benefits of technology

It effectively improves the capacity and volume energy density of the electrochemical device, and at the same time significantly improves the safety performance of nail penetration, reduces the possibility of internal short circuits and short-circuit Joule heat, and reduces the risk of thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833556A_ABST
    Figure CN119833556A_ABST
Patent Text Reader

Abstract

The invention provides an electrochemical device and an electronic device.The electrochemical device comprises a positive pole piece, the positive pole piece comprises a positive current collector, a first coating and a positive material layer, the first coating is arranged on the surface of the positive current collector, and the positive material layer is arranged on the surface, away from the positive current collector, of the first coating; the first coating comprises a first main material and a first binder, the first main material comprises a lithium supplementing material, and the lithium supplementing material comprises at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium orthosilicate or lithium ferrite; the infrared spectrum of the first coating has a characteristic peak between 3200 cm <-1 > and 3400 cm <-1 >. The electrochemical device provided by the invention can give consideration to the safety performance, the capacity and the volume energy density of the cotter pin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art

[0002] Electrochemical devices (such as lithium-ion batteries) have become popular in our daily lives with the development of science and technology. Lithium-ion batteries have entered our daily lives along with the advancement of science and technology and the improvement of environmental protection requirements. With the widespread popularity of lithium-ion batteries, their service life has been increasingly valued by users. Consumers, after-sales service, battery manufacturers and lithium battery manufacturers have all put forward new requirements for the battery's nail penetration safety performance.

[0003] However, with the rapid popularization of lithium-ion batteries, the technology for their product safety is not mature. During use, the positive and negative pole pieces of lithium-ion batteries often come into contact with each other during the nailing process, or the positive and negative pole pieces are connected by nails, resulting in internal short circuits. As people pay more and more attention to the nailing safety performance of lithium-ion batteries, the market is in urgent need of a lithium-ion battery with good nailing safety performance. Summary of the invention

[0004] The purpose of the present application is to provide an electrochemical device and an electronic device. The electrochemical device of the present application can take into account the nail penetration safety performance, capacity and volume energy density.

[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0006] The first aspect of the present application provides an electrochemical device, the electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive current collector, and the positive electrode material layer is arranged on the surface of the first coating away from the positive current collector. The first coating includes a first main material and a first binder, the first main material includes a lithium supplement material, and the lithium supplement material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium orthosilicate or lithium ferrite. The infrared spectrum of the first coating is at 3200cm -1 Up to 3400cm -1 When the electrochemical device has the first coating of the present application, and the selected lithium supplement material is within the above range, the infrared spectrum of the first coating is at 3200cm -1 Up to 3400cm -1When characteristic peaks exist between the two, the lithium-supplementing material can replenish the lithium ions lost by the electrochemical device during the cycle, thereby improving the capacity and volume energy density of the electrochemical device. At the same time, the lithium-supplementing material can form a strong hydrogen bond with the first binder, thereby improving the cohesion and adhesion between the first coating and the positive electrode collector, so that the first coating has a higher mechanical strength, and can protect the positive electrode collector during the nail penetration test, thereby reducing the possibility of short circuit in the electrochemical device, reducing the Joule heat of the short circuit, and reducing the probability of thermal runaway caused by local overheating of the electrochemical device, thereby improving the capacity and volume energy density of the electrochemical device while improving the nail penetration safety performance of the electrochemical device.

[0007] In one embodiment of the present application, at least part of the surface of the lithium supplement material is provided with a first component, the first component includes carbon, nitrogen and oxygen, based on the mass of the first component, the mass percentage of carbon is 63.5% to 73.8%, the mass percentage of nitrogen is 7.6% to 17.9%, and the mass percentage of oxygen is 12% to 24.5%; preferably, based on the mass of the first component, the mass percentage of carbon is 66.25% to 70.1%, the mass percentage of nitrogen is 7.8% to 17.5%, and the mass percentage of oxygen is 12.4% to 22.3%. When the mass percentage of carbon, nitrogen and oxygen based on the first component is within the above range, the oxygen element provides a hydrogen bond donor, so that the bonding group in the binder forms a hydrogen bond with the main material, and the nitrogen element makes the surface of the lithium supplement material have more polar sites, which is conducive to forming a good bond with the binder, and can improve the cohesion and bonding between the first coating and the positive electrode current collector, and improve the nail penetration safety performance of the electrochemical device.

[0008] In one embodiment of the present application, the mass percentage of the first component is 2% to 10% based on the mass of the first main material. When the mass percentage of the first component based on the first main material is within the above range, the first main material has good conductivity, further improves the lithium replenishment capacity, and improves the volume energy density of the electrochemical device.

[0009] In one embodiment of the present application, the Dv50 of the first main material is 50nm to 200nm, preferably 100nm to 150nm. When the particle size of the first main material is within the above range, the first main material with a nanometer particle size can increase the packing density between particles, form a relatively dense first coating on the surface of the positive electrode current collector, improve the crush resistance of the first coating, and enhance the protection of the positive electrode current collector during the nail penetration test, so that the electrochemical device has high capacity and high volume energy density while having good nail penetration safety performance.

[0010] In one embodiment of the present application, based on the mass of the first coating, the mass percentage of the first main material is 84.5% to 94.8%. When the mass percentage of the first component based on the first main material is within the above range, the first coating can have a high compaction density while taking into account the good overall adhesion of the first coating, thereby improving the capacity, volume energy density and nail penetration safety performance of the electrochemical device.

[0011] In one embodiment of the present application, the sphericity of the first main material is 0.705 to 0.874. When the sphericity of the first main material is within the above range, the first main material particles are densely packed with each other, which improves the protection of the positive electrode current collector, reduces the short-circuit Joule heat, and improves the nail penetration safety performance of the electrochemical device.

[0012] In one embodiment of the present application, the first binder includes a water-soluble polymer metal salt; based on the mass of the first coating, the mass percentage of the first binder based on the first coating is 5.2% to 15.5%. When the first binder is selected from the above materials and the mass percentage is within the scope of the present application, the tensile strength of the first coating can be improved, the bonding force between the first coating and the positive electrode current collector can be improved, and the nail penetration safety performance of the electrochemical device can be improved.

[0013] In one embodiment of the present application, the metal element in the water-soluble polymer metal salt includes at least one of lithium, sodium, potassium, rubidium, cesium, francium, beryllium, barium, strontium, calcium or magnesium; the polymer in the water-soluble polymer metal salt includes at least one of polyacrylic acid, carboxymethyl cellulose, polyacrylonitrile or styrene butadiene. When the water-soluble metal salt is selected from the above materials, the tensile strength of the first coating layer can be increased, the bonding force between the first coating layer and the positive electrode current collector can be improved, and the nail penetration safety performance of the electrochemical device can be improved.

[0014] In one embodiment of the present application, the water-soluble polymer metal salt includes at least one of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate, calcium polyacrylate, magnesium polyacrylate, lithium carboxymethyl cellulose or sodium carboxymethyl cellulose. When the water-soluble metal salt is selected from the above materials, the tensile strength of the first coating layer can be increased, the bonding force between the first coating layer and the positive electrode current collector can be improved, and the nail penetration safety performance of the electrochemical device can be improved.

[0015] In one embodiment of the present application, the first coating layer further includes a first conductive agent, which includes at least one of conductive carbon black, activated carbon, carbon nanotubes, or carbon nanofibers; based on the mass of the first coating layer, the mass percentage of the first conductive agent is 0.2% to 0.5%. When the first conductive agent is selected from the above materials and the mass percentage is within the range of the present application, the first coating layer has a high short-circuit resistance and good conductivity, thereby improving the cycle performance of the electrochemical device.

[0016] In one embodiment of the present application, the particle size of the secondary particles of the first conductive agent is less than 50 nm. When the particle size of the secondary particles of the first conductive agent is within the above range, it indicates that the first conductive agent has good dispersibility in the first coating layer, improves the conductivity of the first coating layer, and improves the cycle performance of the electrochemical device.

[0017] In one embodiment of the present application, the thickness of the first coating is 0.2 μm to 2 μm, preferably 0.5 μm to 2 μm. When the thickness of the first coating is within the above range, the first coating has a higher mechanical strength, and improves the nail penetration safety performance of the electrochemical device.

[0018] In one embodiment of the present application, the bonding force between the first coating and the positive electrode current collector is F1, 500N / m≤F1≤900N / m. For example, F1 can be 500N / m, 600N / m, 700N / m, 800N / m, 900N / m, or a range consisting of any two values ​​therein. When the bonding force F1 between the first coating and the positive electrode current collector is within the above range, it indicates that the first coating and the positive electrode current collector have good bonding, thereby improving the nail penetration safety performance and cycle performance of the electrochemical device.

[0019] In one embodiment of the present application, the cohesive force of the first coating is F2, 1400N / m≤F2≤2500N / m. For example, F2 can be 1400N / m, 1500N / m, 2000N / m, 2500N / m, or a range consisting of any two values ​​therein. When the cohesive force F2 of the first coating is within the above range, the first coating as a whole has strong adhesion, which can improve the adhesion between the first coating and the positive electrode current collector, thereby improving the nail penetration safety performance of the electrochemical device.

[0020] In one embodiment of the present application, the membrane resistance of the positive electrode sheet is 0.5Ω to 5Ω. For example, the membrane resistance of the positive electrode sheet can be 0.5Ω, 1Ω, 2Ω, 3Ω, 4Ω, 5Ω, or a range consisting of any two values ​​therein. When the membrane resistance of the positive electrode sheet is within the above range, the positive electrode sheet has good conductivity and improves the cycle performance of the electrochemical device.

[0021] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has good nail penetration safety performance and high capacity and volume energy density.

[0022] Beneficial effects of this application:

[0023] The present application provides an electrochemical device and an electronic device, wherein the electrochemical device comprises a positive electrode plate, wherein the positive electrode plate comprises a positive current collector, a first coating and a positive electrode material layer, wherein the first coating is disposed on the surface of the positive current collector, and the positive electrode material layer is disposed on the surface of the first coating away from the positive current collector. The first coating comprises a first main material and a first binder, wherein the first main material comprises a lithium supplement material, wherein the lithium supplement material comprises at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium orthosilicate or lithium ferrite. The infrared spectrum of the first coating is at 3200cm -1 Up to 3400cm -1 When the electrochemical device has the first coating of the present application, and the selected lithium supplement material is within the above range, the infrared spectrum of the first coating is at 3200cm -1 Up to 3400cm -1 When there are characteristic peaks between them, the lithium-supplementing material can replenish the lithium ions lost by the electrochemical device during the cycle, and improve the capacity and volume energy density of the electrochemical device. At the same time, the lithium-supplementing material can form a strong hydrogen bond with the first binder, thereby improving the cohesion and adhesion between the first coating and the positive electrode collector, so that the first coating has a higher mechanical strength, which can protect the positive electrode collector during the nail penetration test, reduce the possibility of short circuit in the electrochemical device, reduce the short circuit Joule heat, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the nail penetration safety performance of the electrochemical device.

[0024] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0026] Figure 1 A schematic diagram of the positive electrode structure of an embodiment of the present application;

[0027] Figure 2 This is the infrared spectrum test chart of the first coating of Example 1-1;

[0028] Figure 3 This is the infrared spectrum test chart of the first coating of Comparative Example 2;

[0029] Figure 4 This is a scanning electron microscope image of a cross section of a positive electrode sheet according to an embodiment of the present application. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0031] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0032] The first aspect of the present application provides an electrochemical device, the electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive current collector, and the positive electrode material layer is arranged on the surface of the first coating away from the positive current collector. The first coating includes a first main material and a first binder, the first main material includes a lithium supplement material, and the lithium supplement material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium orthosilicate or lithium ferrite. The infrared spectrum of the first coating is at 3200cm -1 Up to 3400cm -1 When the electrochemical device has the first coating of the present application, and the selected lithium supplement material is within the above range, the infrared spectrum of the first coating is at 3200cm -1 Up to 3400cm -1 When characteristic peaks exist between the two, the lithium-supplementing material can replenish the lithium ions lost by the electrochemical device during the cycle, thereby improving the capacity and volume energy density of the electrochemical device. At the same time, the lithium-supplementing material can form a strong hydrogen bond with the first binder, thereby improving the cohesion and adhesion between the first coating and the positive electrode collector, so that the first coating has a higher mechanical strength, and can protect the positive electrode collector during the nail penetration test, thereby reducing the possibility of short circuit in the electrochemical device, reducing the Joule heat of the short circuit, reducing the probability of thermal runaway caused by local overheating of the electrochemical device, and improving the nail penetration safety performance of the electrochemical device.

[0033] In this application, the above-mentioned “the first coating is disposed on the surface of the positive electrode current collector” means that the first coating can be disposed on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the “surface” here can be the entire area of ​​the positive electrode current collector, or it can be a partial area of ​​the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. Specifically, if Figure 1 As shown, a first coating layer 12 and a positive electrode material layer 13 are sequentially stacked on the two surfaces of the positive electrode current collector 11. The above-mentioned "the positive electrode material layer is arranged on the surface of the first coating layer away from the positive electrode current collector" can be understood by analogy.

[0034] In one embodiment of the present application, a first component is provided on at least part of the surface of the lithium supplement material, and the first component includes carbon, nitrogen and oxygen. Based on the mass of the first component, the mass percentage of the carbon element is 63.5% to 73.8%, the mass percentage of the nitrogen element is 7.6% to 17.9%, and the mass percentage of the oxygen element is 12% to 24.5%; preferably, based on the mass of the first component, the mass percentage of the carbon element is 66.25% to 70.1%, the mass percentage of the nitrogen element is 7.8% to 17.5%, and the mass percentage of the oxygen element is 12.4% to 22.3%. For example, the mass percentage of carbon element based on the first component can be 63.5%, 65%, 66.25%, 67%, 69%, 70.1%, 71%, 73%, 73.8% or a range consisting of any two of these values; the mass percentage of nitrogen element based on the first component can be 7.6%, 7.8%, 8%, 10%, 12%, 14%, 16%, 17.5%, 17.9% or a range consisting of any two of these values; the mass percentage of oxygen element based on the first component can be 12%, 12.4%, 13%, 14%, 15%, 16%, 17%, 18%, 18.6%, 20%, 22.3%, 24%, 24.5% or a range consisting of any two of these values. When the mass percentage of carbon, nitrogen and oxygen based on the first component is within the above range, the oxygen element provides a hydrogen bond donor, so that the bonding groups in the binder form hydrogen bonds with the main material. The nitrogen element allows more polar sites to exist on the surface of the lithium supplement material, which is conducive to forming a good bond with the binder, thereby improving the cohesion and adhesion between the first coating and the positive electrode collector, protecting the positive electrode collector during the nail penetration test, reducing the possibility of short circuit in the electrochemical device, reducing the Joule heat of the short circuit, reducing the probability of thermal runaway caused by local overheating of the electrochemical device, and improving the nail penetration safety performance of the electrochemical device.

[0035] In one embodiment of the present application, the mass percentage of the first component is 2% to 10% based on the mass of the first main material. For example, the mass percentage of the first component based on the first main material can be 2%, 4%, 6%, 8%, 10% or a range consisting of any two of these values. When the mass percentage of the first component based on the first main material is within the above range, the first main material has good conductivity, further improves the lithium replenishment capacity, and improves the capacity and volume energy density of the electrochemical device.

[0036] In one embodiment of the present application, the Dv50 of the first main material is 50nm to 200nm, preferably 100nm to 150nm. For example, the Dv50 of the first main material can be 50nm, 100nm, 150nm, 200nm or a range consisting of any two values ​​therein. When the particle size of the first main material is within the above range, the first main material with nanometer particle size can increase the packing density between particles, form a denser first coating on the surface of the positive electrode collector, improve the crush resistance of the first coating, enhance the protection of the positive electrode collector during the nail penetration test, wrap the metal burrs that may be generated by the positive electrode collector in the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, and at the same time, the first coating has a higher compaction density, reducing energy density loss, thereby making the electrochemical device have high capacity and high volume energy density while having good nail penetration safety performance.

[0037] In the present application, Dv50 means a particle size at which the volume accumulation is 50% from the smaller particle size side in the volume-based particle size distribution of the first main material.

[0038] In one embodiment of the present application, based on the mass of the first coating, the mass percentage of the first main material is 84.5% to 94.8%. For example, the mass percentage of the first main material based on the first coating can be 84.5%, 85%, 90%, 94%, 94.8% or a range consisting of any two of these values. When the mass percentage of the first component based on the first main material is within the above range, the first coating can have a high compaction density while taking into account the good overall adhesion of the first coating, thereby improving the capacity, volume energy density and nail penetration safety performance of the electrochemical device.

[0039] In one embodiment of the present application, the sphericity of the first main material is 0.705 to 0.874. For example, the sphericity of the first main material can be 0.705, 0.71, 0.75, 0.79, 0.83, 0.87, 0.874 or a range consisting of any two of these values. When the sphericity of the first main material is within the above range, it is conducive to the inlay bite between the particles of the first main material, and the packing density of the first main material is increased. During the nail penetration test, when the first coating is mechanically abused and damaged, it is not easy to produce relative slip between the particles of the first main material, thereby improving the protection of the positive electrode current collector, reducing short-circuit Joule heat, and improving the nail penetration safety performance of the electrochemical device.

[0040] In one embodiment of the present application, the first binder includes a water-soluble polymer metal salt; based on the mass of the first coating, the mass percentage of the first binder based on the first coating is 5.2% to 15.5%. For example, the mass percentage of the first binder can be 5.2%, 7%, 9%, 11%, 15%, 15.5%, or a range consisting of any two of these values. When the first binder is selected from the above materials and the mass percentage is within the scope of the present application, the overall adhesion of the first coating can be improved, and the adhesion between the first coating and the positive current collector can be improved, thereby improving the nail penetration safety performance of the electrochemical device.

[0041] In one embodiment of the present application, the metal element in the water-soluble polymer metal salt includes at least one of lithium, sodium, potassium, rubidium, cesium, francium, beryllium, barium, strontium, calcium or magnesium; the polymer in the water-soluble polymer metal salt includes at least one of polyacrylic acid, carboxymethyl cellulose, polyacrylonitrile or styrene butadiene. When the water-soluble metal salt is selected from the above materials, the water-soluble metal salt compound has good hydrophilicity, which is conducive to the transmission of electrons and ions, and the electronic conductivity and ionic conductivity are better than those of non-water-soluble polymers such as polyvinylidene fluoride and polyvinylidene chloride, so the first coating can improve the kinetic performance of the electrochemical device and improve the cycle performance of the electrochemical device; in addition, the water-soluble metal salt compound has a large specific surface area and can be highly dispersed after encountering water. It is applied to the first coating as a binder, which can improve the tensile strength of the first coating. At the same time, the water-soluble metal salt compound has many polar functional groups, which can further enhance the bonding force between the first coating and the positive electrode current collector through hydrogen bonds, and improve the nail penetration safety performance of the electrochemical device.

[0042] In one embodiment of the present application, the water-soluble polymer metal salt includes at least one of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate, calcium polyacrylate, magnesium polyacrylate, lithium carboxymethyl cellulose or sodium carboxymethyl cellulose. When the water-soluble metal salt is selected from the above materials, the adhesion of the first coating as a whole can be improved, and the adhesion between the first coating and the positive electrode current collector can be improved, thereby improving the nail penetration safety performance of the electrochemical device.

[0043] In one embodiment of the present application, the first coating layer further includes a first conductive agent, and the first conductive agent includes at least one of conductive carbon black, activated carbon, carbon nanotubes or carbon nanofibers; based on the mass of the first coating layer, the mass percentage of the first conductive agent is 0.2% to 0.5%. For example, the mass percentage of the first conductive agent based on the first coating layer can be 0.2%, 0.3%, 0.4%, 0.5% or a range consisting of any two of these values. When the first conductive agent is selected from the above materials and the mass percentage is within the scope of the present application, the first coating layer has a high short-circuit resistance and good conductivity, thereby improving the cycle performance of the electrochemical device.

[0044] In one embodiment of the present application, the cross section of the first coating along the thickness direction is within the range of 4μm×4μm in the scanning electron microscope image with a magnification of 30,000 times, and the particle size of the secondary particles of the first conductive agent is less than 50nm. For example, the particle size of the secondary particles of the first conductive agent can be 1nm, 10nm, 20nm, 30nm, 40nm, 49nm or a range consisting of any two values ​​therein. During the preparation process of the first coating, the particle size of the first conductive agent particles is relatively small and it is easy to aggregate to form secondary particles of the first conductive agent. When the particle size of the secondary particles is less than 50nm, it cannot be observed in the scanning electron microscope image of the cross section of the first coating, indicating that the secondary particles are more evenly dispersed in the first coating, and there is no agglomeration to form secondary particles with larger particle size, thereby improving the conductivity of the first coating and enhancing the cycle performance of the electrochemical device.

[0045] In one embodiment of the present application, the thickness of the first coating is 0.2 μm to 2 μm, preferably 0.5 μm to 2 μm. For example, the thickness of the first coating can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 0.95 μm, 1 μm, 1.5 μm, 2 μm or a range consisting of any two of the values. When the thickness of the first coating is within the above range, the first coating has a high mechanical strength, can protect the positive electrode current collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway caused by local overheating of the electrochemical device, and improve the nail penetration safety performance of the electrochemical device.

[0046] In one embodiment of the present application, the bonding force between the first coating and the positive electrode current collector is F1, 500N / m≤F1≤900N / m. For example, F1 can be 500N / m, 600N / m, 700N / m, 800N / m, 900N / m or a range consisting of any two values ​​therein. When the bonding force F1 between the first coating and the positive electrode current collector is within the above range, it means that the first coating and the positive electrode current collector have good bonding, and the first coating can wrap the metal burrs that may be generated in the positive electrode current collector under abnormal conditions such as nail penetration and impact, so as to reduce the occurrence of short circuits in the electrochemical device. At the same time, the probability of thermal runaway or overheating caused by local overheating of the electrochemical device can be reduced, and the nail penetration safety performance of the electrochemical device can be improved. On the other hand, since the volume of the positive electrode material layer will expand during the cycle, the first coating with a strong bonding force can alleviate the deformation of the positive electrode current collector during the cycle, reduce the contact between the positive electrode current collector and the positive electrode material layer, and improve the cycle performance of the electrochemical device.

[0047] In one embodiment of the present application, the cohesive force of the first coating is F2, 1400N / m≤F2≤2500N / m. For example, F2 can be 1400N / m, 1500N / m, 2000N / m, 2500N / m, or a range consisting of any two values ​​therein. When the cohesive force F2 of the first coating is within the above range, the first coating as a whole has strong adhesion, which can improve the adhesion between the first coating and the positive electrode current collector, thereby improving the nail penetration safety performance of the electrochemical device.

[0048] In one embodiment of the present application, the membrane resistance of the positive electrode sheet is 0.5Ω to 5Ω. For example, the membrane resistance of the positive electrode sheet can be 0.5Ω, 1Ω, 2Ω, 3Ω, 4Ω, 5Ω, or a range consisting of any two values ​​therein. When the membrane resistance of the positive electrode sheet is within the above range, the positive electrode sheet has good conductivity and improves the cycle performance of the electrochemical device.

[0049] The present application has no particular restrictions on the preparation method of the first main material, as long as the purpose of the present application can be achieved. For example, the preparation method of the first main material may include but is not limited to the following steps: taking a lithium supplement material and an organic compound precursor with a mass ratio of 70:30 to 90:10, calcining at 300°C to 400°C in a nitrogen atmosphere, and obtaining the first main material after ball milling.

[0050] The organic compound precursor may include but is not limited to at least one of phenolic resin, polyacrylonitrile, polyethyleneimine, hexamethylenetetramine or urea.

[0051] The present application has no particular restrictions on the method for regulating the mass percentage of the carbon element based on the first component, as long as the purpose of the present application can be achieved. For example, it can be regulated by regulating the mass ratio of the organic compound precursor and the lithium-supplementing material. Exemplarily, the mass ratio of the organic compound precursor and the lithium-supplementing material increases, the mass percentage of the carbon element based on the first component increases, the mass ratio of the organic compound precursor and the lithium-supplementing material decreases, and the mass percentage of the carbon element based on the first component decreases. In addition, the mass percentage of the carbon element based on the first component can also be regulated by the type of organic compound precursor.

[0052] The present application has no particular restrictions on the method for regulating the mass percentage of nitrogen based on the first component, as long as the purpose of the present application can be achieved. For example, it can be regulated by the calcination temperature. For example, as the calcination temperature increases, the mass percentage of nitrogen based on the first component increases, and as the calcination temperature decreases, the mass percentage of nitrogen based on the first component decreases.

[0053] The present application has no particular restrictions on the method for regulating the mass percentage of oxygen based on the first component, as long as the purpose of the present application can be achieved. For example, the regulation can be performed by regulating the calcination temperature. For example, as the calcination temperature increases, the mass percentage of oxygen based on the first component decreases, and as the calcination temperature decreases, the mass percentage of oxygen based on the first component increases.

[0054] The present application has no particular restrictions on the method for regulating the mass percentage of the first component based on the first main material, as long as the purpose of the present application can be achieved. For example, it can be regulated by regulating the mass ratio of the organic compound precursor and the lithium-supplementing material. Exemplarily, the mass ratio of the organic compound precursor and the lithium-supplementing material increases, the mass percentage of the first component based on the first main material increases, the mass ratio of the organic compound precursor and the lithium-supplementing material decreases, and the mass percentage of the first component based on the first main material decreases.

[0055] The present application has no particular restrictions on the method for regulating the Dv50 of the first main material, as long as the purpose of the present application can be achieved. For example, it can be regulated by regulating the time of ball milling. Exemplarily, when the time of ball milling increases, the Dv50 of the first main material decreases, and when the time of ball milling decreases, the Dv50 of the first main material increases.

[0056] The present application has no particular restrictions on the method for regulating the sphericity of the first main material, as long as the purpose of the present application can be achieved. For example, the sphericity of the lithium supplement material can be regulated. The lithium supplement materials with different sphericities in the present application can be purchased, and the sphericity of the lithium supplement material can be tested in combination with the "sphericity test" test method provided in the present application to select the lithium supplement material with the required sphericity.

[0057] In one embodiment of the present application, the first coating includes a first main material and a first binder. Based on the mass of the first coating, the mass percentage of the first main material is 84.5% to 94.8%, and the mass percentage of the first binder is 5.2% to 15.5%.

[0058] In one embodiment of the present application, the first coating includes a first main material, a first binder and a first conductive agent. Based on the mass of the first coating, the mass percentage of the first main material is 84.5% to 94.8%, the mass percentage of the first binder is 5% to 15%, and the mass percentage of the first conductive agent is 0.2% to 0.5%.

[0059] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet may include but is not limited to the following steps: the first main material and the first binder are mixed in a mass ratio of (84.5 to 94.8): (5.2 to 15.5), deionized water is added as a solvent, and stirred evenly to obtain a first coating slurry with a solid content of 70wt% to 80wt%; or, the first main material, the first binder and the first conductive agent are mixed in a mass ratio of (84.5 to 94.8): (5 to 15): (0.2 to 0.5), deionized water is added as a solvent, and stirred evenly to obtain a first coating slurry with a solid content of 70wt% to 80wt%. Then the first coating slurry is coated on one surface of the positive electrode current collector of 5μm to 20μm, and baked at 90℃ to 180℃ for 1h to 3h to obtain a first coating with a thickness of 0.2μm to 2μm. Then, a positive electrode material layer slurry is prepared, and the positive electrode material layer slurry is coated on the surface of the first coating layer, and dried to obtain a positive electrode sheet coated with the first coating layer and the positive electrode material layer on one side. The above steps are repeated on the other surface of the positive electrode current collector to obtain a positive electrode sheet coated with the first coating layer and the positive electrode material layer on both sides.

[0060] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0061] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to at least one of lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.

[0062] The positive electrode material layer may also include a second conductive agent and a second binder. The present application does not particularly limit the types of the second conductive agent and the second binder, as long as the purpose of the present application can be achieved. For example, the second conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the second binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the second conductive agent, and the second binder in the positive electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0063] The thickness of the positive electrode current collector is not particularly limited in the present application, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm.

[0064] In the present application, the electrochemical device also includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the surface of the negative electrode current collector, or it can be a partial area of ​​the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0065] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector or a titanium-copper composite current collector, etc.

[0066] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.

[0067] In some embodiments of the present application, the negative electrode material layer may further include a second conductive agent and a second binder, for example, at least one of the above-mentioned second conductive agent and the above-mentioned second binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the second conductive agent, and the second binder in the negative electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0068] The present application has no particular limitation on the thickness of the negative electrode material layer and the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 80 μm to 100 μm, and the thickness of the negative electrode current collector is 4 μm to 15 μm.

[0069] Optionally, the negative electrode plate may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it may be a conductive layer commonly used in the art. For example, the conductive layer includes a second conductive agent and a second binder. The present application has no particular restrictions on the second conductive agent and the second binder in the conductive layer, and for example, it may be at least one of the above-mentioned second conductive agent and the above-mentioned second binder.

[0070] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) membranes), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0071] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.

[0072] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.

[0073] In some embodiments of the present application, the inorganic layer includes ceramic particles and a second binder. The present application has no particular restrictions on ceramic particles, such as ceramic particles may include at least one of silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the second binder, such as the second binder may be at least one of the above-mentioned second binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).

[0074] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.

[0075] In the present application, the electrochemical device further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.

[0076] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.

[0077] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.

[0078] The carbonate compound may include but is not limited to at least one of a chain carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The chain carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0079] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.

[0080] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.

[0081] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has good nail penetration safety performance and high capacity and volume energy density.

[0082] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0083] Example

[0084] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.

[0085] Test methods and equipment:

[0086] First main material Dv50 test

[0087] The lithium-ion batteries in the embodiments and comparative examples were disassembled to obtain positive electrode sheets. The disassembled positive electrode sheets were sintered into powder at 400° C. in air, and the particle size was tested using a particle size analyzer to obtain the Dv50 of the first main material.

[0088] Sphericity test

[0089] A Malvern automatic image particle size analyzer is used to capture and process images of a certain number (greater than 5,000) of dispersed lithium supplement material particles or first main material particles, and then the image-guided Raman spectroscopy (MDRS) is used to accurately analyze the microstructure and morphology of the particles, obtain the longest diameter and shortest diameter of all particles, calculate the ratio of the shortest diameter to the longest diameter of each particle to obtain the sphericity of each particle, and take the average of the sphericity of all particles as the average sphericity. In this application, the sphericity of the lithium supplement material refers to the average sphericity of the lithium supplement material, and the sphericity of the first main material refers to the average sphericity of the first main material.

[0090] Scanning electron microscope test

[0091] The positive electrode sheet is plasma cut longitudinally along the thickness direction, polished by argon ion polishing technology to obtain a flat cross section, and then a scanning electron microscope (OXFORD·EDS) is used to observe the cross section of the positive electrode sheet at a magnification of 30,000 times and within a range of 4μm×4μm. If the secondary particles of the first conductive agent cannot be observed, the particle size of the secondary particles of the first conductive agent is recorded as "<50nm". If the secondary particles of the first conductive agent can be observed, the particle size of the secondary particles of the first conductive agent is recorded as "≥50nm". Among them, the scanning electron microscope image of the cross section of the positive electrode sheet of Example 1-1 is as follows: Figure 4 shown.

[0092] Carbon, nitrogen and oxygen content test

[0093] (1) After the lithium-ion battery is discharged to 3V at 0.2C, the positive electrode sheet is removed and cut into 10 small discs with a diameter of 16 mm. After scraping off the positive electrode material layer with a knife, the first coating is scraped off from the positive electrode current collector of a single small disc to obtain the first coating powder. The first coating powder is mixed with water and centrifuged at 3500rpm to remove the lower layer powder, which is the first main material. 0.2g of the first main material is weighed and digested with 10mL of aqua regia, and diluted to a 100mL volumetric flask with deionized water. An inductively coupled plasma analyzer (ICP, model AVIO-200) was used to set the radio frequency generator (RF) frequency to 40.68 MHz, the argon secondary pressure to 0.6 MPa, the RF power to 1400 W, and the pump speed to 1.0 mL / min. The contents of carbon, nitrogen, and oxygen in the first main material of a single small disc were tested. The contents of carbon, nitrogen, and oxygen obtained from the above 10 small discs were averaged to obtain the mass percentage content W of carbon, nitrogen, and oxygen in the first main material. C , W N and W O Among them, aqua regia is obtained by mixing concentrated nitric acid and concentrated hydrochloric acid in a volume ratio of 1:1.

[0094] (2) The mass percentage of carbon in the first main material is recorded as W1, the mass percentage of nitrogen is recorded as W2, the mass percentage of oxygen is recorded as W3, and the mass percentage of carbon in the first component is W C =W1 / (W1+W2+W3), the mass percentage of nitrogen in the first component W N =W2 / (W1+W2+W3), the mass percentage of oxygen in the first component W O =W3 / (W1+W2+W3).

[0095] Infrared spectrum test

[0096] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, and the lithium-ion battery was disassembled to obtain the positive electrode sheet, which was cleaned with dimethyl carbonate (DMC) for 10 minutes, and then baked at 100°C for 2 hours for standby use. The positive electrode material layer on the positive electrode sheet was scraped off to obtain a positive current collector with a first coating on the surface.

[0097] The infrared spectrum of the positive electrode current collector coated with the first coating on the surface was tested by an infrared spectrometer (model: Nicolet iS50) using a potassium bromide (KBr) tablet method. The infrared spectrum of the first coating of Example 1-1 is shown in FIG. Figure 2 As shown, the infrared spectrum of the first coating of Comparative Example 2 is as follows Figure 3 shown.

[0098] First coating thickness test

[0099] The positive electrode sheet was plasma cut longitudinally along the thickness direction and polished by argon ion polishing technology to obtain a flat cross section. Then, a scanning electron microscope (OXFORD·EDS) was used with a magnification of 40,000 times to observe and measure the thickness of the first coating at three locations. The average value was taken as the thickness of the first coating.

[0100] Nail penetration test

[0101] Take 10 lithium-ion batteries in the embodiment or comparative example and fully charge them at 25±3°C. The specific steps are: charge at a constant current of 0.5C to 4.5V, and then charge at a constant voltage of 4.5V to a current cutoff of 0.05C.

[0102] The nail penetration test was conducted on lithium-ion batteries at 25±3℃, using a steel nail with a diameter of 4mm, made of carbon steel, with a taper of 16.5mm, and a total length of 100mm. The nail penetration speed was set to 30mm / s, and the nail penetration depth was based on the taper of the steel nail passing through the lithium-ion battery. The state of the lithium-ion battery was observed during the test, and the judgment standard was whether the lithium-ion battery burned or exploded. The pass rate of the nail penetration test = the number of lithium-ion batteries that did not burn or explode during the nail penetration test / 10×100%.

[0103] Cohesion test

[0104] The part of the positive electrode plate coated with only the first coating was punched out with a mold to obtain a test strip with a length of 120 mm and a width of 30 mm. Wipe the surface of the steel plate clean with alcohol, and stick a double-sided tape (NITTO, NO5000NS) with a length of 100 mm and a width of 20 mm on the steel plate. Stick the test strip in the center on the double-sided tape with the test surface facing down. Stick the green glue (Todi adhesive tape, 100 mm long and 20 mm wide) in the center on the test strip, take a paper tape with a length of 100 mm and a width of 30 mm, and insert the paper tape between the test strip and the green glue, with a cross-overlap length of 15 mm. Push a rubber roller with a mass of 2 kg by hand to roll back and forth on the test strip 4 times to obtain a test sample. Use a tensile tester (Sansi, Instron 3365) to test the test sample. Fix the test sample on the test bench, then fold the paper tape 180° upwards and fix it with a clamp. Then the tensile machine slowly pulls the paper tape at a speed of 10mm / min until the green glue is separated from the first coating on the surface of the positive electrode. The test ends. The average tensile force in the stable area is recorded as the cohesive force F2 of the first coating, in N / m.

[0105] Adhesion test

[0106] Take the positive electrode plate coated with the first coating, stick the positive electrode plate on a smooth steel plate with double-sided tape, stick the other side of the positive electrode plate with adhesive tape, and fix one end of the adhesive tape on the tensile testing machine. Set the speed to 10 mm / min, and start pulling the adhesive tape at 180° with the tensile testing machine. Use the sensor to dynamically read the bonding force of the adhesive tape when it is stretched, export the data, take the average and divide it by the width of the adhesive tape to obtain the bonding force F1 between the first coating and the positive current collector.

[0107] Diaphragm resistance test

[0108] The portion of the positive electrode current collector surface coated with the first coating and the positive electrode material layer was cut into a test sample with a size of 60 mm×80 mm. The diaphragm resistance of the positive electrode sheet was tested using a diaphragm resistance meter with a test pressure of 0.4 T and a holding time of 10 s.

[0109] Discharge capacity test

[0110] The lithium-ion battery was placed in an environment of 25°C, charged to 4.5V at a constant current of 1C, and charged to 0.05C at a constant voltage of 4.5V; the lithium-ion battery was left to stand for 10 minutes, and discharged to a discharge cut-off voltage of 3.0V at a constant current of 0.2C, and the discharge capacity of the lithium-ion battery was measured.

[0111] Volumetric energy density test

[0112] At 25°C, charge the lithium-ion battery at a constant current of 1C to 4.5V, then charge at a constant voltage of 4.5V to a current of 0.05C, and then discharge at 0.5C to 3.0V. Record the capacity at this time as D. Measure the length, width and thickness of the lithium-ion battery at this time, and calculate the volume V of the lithium-ion battery. At the same time, the discharge voltage platform P of the lithium-ion battery can be obtained. The volume energy density of the lithium-ion battery is: VED=D×P / V, in Wh / L.

[0113] Example 1-1

[0114] <Preparation of the first main material>

[0115] The lithium supplement material LiFePO4 and the organic precursor phenolic resin in a mass ratio of 90:10 were calcined at 350°C in a nitrogen atmosphere, and the first main material was obtained after ball milling. The sphericity of the first main material was 0.71, and the particle size Dv50 of the first main material was 125nm; based on the mass of the first main material, the mass percentage of the first component was 3%; based on the mass of the first component, the mass percentage of the carbon element W C The mass percentage of nitrogen is 68.65%. N The mass percentage of oxygen is 12.75%. O It is 18.6%.

[0116] <Preparation of positive electrode sheet>

[0117] The first main material and the first binder sodium polyacrylate prepared above were mixed in a mass ratio of 91:9, deionized water was added as a solvent, and the mixture was stirred evenly to obtain a first coating slurry with a solid content of 75wt%, which was coated on one surface of an 8μm positive electrode current collector aluminum foil, and dried at 120°C to obtain a first coating with a thickness of 0.95μm. The positive electrode active material lithium cobalt oxide, the second conductive agent carbon nanotube (CNT), and the second binder polyvinylidene fluoride were mixed in a mass ratio of 97.3:1.1:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry was evenly coated on the surface of the first coating, and dried at 120°C to obtain a positive electrode sheet coated with the first coating and the positive electrode material layer on one side, and the coating weight of the positive electrode material layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil, and after drying at 120°C, a positive electrode sheet coated with the first coating and the positive electrode material layer on both sides is obtained. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 90μm.

[0118] The schematic diagram of the structure of the positive electrode sheet prepared in Example 1-1 is as follows Figure 1 shown.

[0119] <Preparation of negative electrode sheet>

[0120] The negative electrode active material artificial graphite, the second binder styrene butadiene rubber (SBR) and the second binder carboxymethyl cellulose (CMC) were mixed at a mass ratio of 97.7:1:1.3, and then deionized water was added as a solvent to prepare a slurry with a solid content of 70wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided negative electrode material layer. The coating weight of the negative electrode material layer was 142mg / 1540mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. The thickness of the single-sided negative electrode material layer is 85μm.

[0121] <Preparation of Electrolyte>

[0122] In an argon atmosphere glove box with a water content of less than 10ppm, carbonate compounds ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of 10:30:60 to obtain a basic solvent, and lithium salt LiPF6 was added and stirred evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the remainder is the basic solvent.

[0123] <Isolation film>

[0124] A polyethylene porous polymer film with a thickness of 8 μm (manufacturer: Celgard Membrane Co., Ltd., USA) was used as a separator.

[0125] <Preparation of lithium-ion batteries>

[0126] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound, and the electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, and shaping processes, a lithium-ion battery is obtained. The upper limit voltage of the formation is 4.53V, the formation temperature is 85°C, and the formation time is 50min.

[0127] Example 1-2 to Example 1-3

[0128] Except that in <Preparation of the First Main Material>, lithium supplement materials with different sphericities are selected so that the sphericity of the first main material is as shown in Table 1, the rest is the same as Example 1-1.

[0129] Example 1-4 to Example 1-9

[0130] Except that the ball milling time is adjusted in <Preparation of the first main material> so that the Dv50 of the first main material is as shown in Table 1, the rest is the same as Example 1-1.

[0131] Example 1-10 to Example 1-14

[0132] Except for adjusting the mass ratio of the lithium supplement material and the organic precursor in <Preparation of the First Main Material> so that the mass percentage of the first component is as shown in Table 1, the rest is the same as Example 1-1.

[0133] Example 1-15 to Example 1-23

[0134] Except for adjusting the type of organic precursor, the mass ratio of lithium supplement material and organic precursor and the calcination temperature in <Preparation of the first main material> so that the mass percentage of carbon element, the mass percentage of nitrogen element and the mass percentage of oxygen element are as shown in Table 1, the rest is the same as Example 1-1. Among them, Examples 1-17 to 1-18 and Examples 1-21 to 1-22 use polyurethane as the organic compound precursor.

[0135] Example 1-24 to Example 1-29

[0136] Except for adjusting the thickness of the first coating layer according to Table 1, the rest is the same as Example 1-1.

[0137] Example 2-1 to Example 2-8

[0138] In the preparation of the positive electrode plate, except that the first conductive agent conductive carbon black is added to the first coating slurry, and the mass percentage of the first conductive agent, the mass percentage of the first main material and the mass percentage of the first binder are adjusted according to Table 2, the rest is the same as Example 1-1.

[0139] Example 2-9 to Example 2-12

[0140] Except for adjusting the type of lithium supplementing material and the type of the first binder according to Table 2, the rest is the same as Example 1-1.

[0141] Comparative Example 1

[0142] Except that the first coating layer is not provided on the surface of the positive electrode current collector, the rest is the same as Example 1-1.

[0143] Comparative Example 2

[0144] In the preparation of the first main material, polyurethane is used as an organic compound precursor, and the calcination temperature is adjusted so that the mass percentage of carbon, the mass percentage of nitrogen, and the mass percentage of oxygen are as shown in Tables 1 and 2, and the infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm -1 Except that there is no characteristic peak, the rest is the same as Example 1-1.

[0145] Comparative Example 3

[0146] Except that in <Preparation of the First Main Material>, aluminum oxide with a particle size of 125 nm and a sphericity of 0.71 is directly used as the first main material, and the preparation parameters are adjusted according to Tables 1 and 2, the rest is the same as Example 1-1.

[0147] Comparative Example 4

[0148] Except that in <Preparation of the First Main Material>, boehmite with a particle size of 125 nm and a sphericity of 0.71 is directly used as the first main material and the preparation parameters are adjusted according to Tables 1 and 2, the rest is the same as Example 1-1.

[0149] The preparation parameters and performance tests of various embodiments and comparative examples are shown in Tables 1 and 2.

[0150] Table 1

[0151] Note: “ / ” in Table 1 means that there is no corresponding preparation parameter or substance. C Indicates the mass percentage of carbon element based on the first component, W N Indicates the mass percentage of nitrogen based on the first component, W O represents the mass percentage of oxygen element based on the first component, F1 represents the bonding force between the first coating and the positive electrode current collector, F2 represents the cohesive force of the first coating, and the infrared spectrum characteristic peak refers to the infrared spectrum of the first coating at 3200cm -1 Up to 3400cm -1 The characteristic peaks between .

[0152] Table 2

[0153] Note: “ / ” in Table 2 means that there is no corresponding preparation parameter or substance. ZC Indicates the mass percentage of the first main material, W DD represents the mass percentage of the first conductive agent, W NJ represents the mass percentage of the first binder, F1 represents the bonding force between the first coating and the positive electrode current collector, F2 represents the cohesive force of the first coating, and the infrared spectrum characteristic peak refers to the infrared spectrum of the first coating at 3200cm -1 Up to 3400cm -1 The characteristic peaks between .

[0154] It can be seen from Examples 1-1 to 1-29 and Comparative Examples 1 to 4 that when the positive electrode sheet has the structure of the first coating of the present application and the infrared spectrum of the first coating is at 3200 cm -1 Up to 3400cm -1 When there are characteristic peaks between the first coating layer and the positive electrode current collector, the cohesive force of the first coating layer is high, the bonding force between the first coating layer and the positive electrode current collector is high, the obtained lithium-ion battery capacity and volume energy density are high, and the pass rate of the nail penetration test is high, which shows that the lithium-ion battery of the present application can take into account the capacity, volume energy density and nail penetration safety performance. The positive electrode sheet in Comparative Example 1 does not have the first coating structure of the present application. The infrared spectrum of the first coating layer in Comparative Example 2 is at 3200cm-1 Up to 3400cm -1 There is no characteristic peak between them. The first main material of Comparative Example 3 is aluminum oxide, and the first main material of Comparative Example 4 is boehmite. The surface of boehmite contains hydroxyl functional groups, and the first coating has a peak at 3200cm -1 Up to 3400cm -1 There are characteristic peaks between them, and the obtained lithium-ion battery capacity and volume energy density are low or the pass rate of the nail penetration test is low, and it is impossible to take into account the nail penetration safety performance, capacity and volume energy density.

[0155] Figure 2 The infrared spectrum of the first coating of Example 1-1 is at 3200 cm -1 Up to 3400cm -1 There are characteristic peaks between them. Figure 3 The infrared spectrum of the first coating of Comparative Example 2 is at 3200 cm -1 Up to 3400cm -1 There are no characteristic peaks between them.

[0156] The sphericity of the first main material usually affects the capacity, volume energy density and nail penetration safety performance of the lithium-ion battery. It can be seen from Examples 1-1 to 1-3 that when the sphericity of the first main material is within the scope of this application, the cohesion of the first coating is high, the adhesion between the first coating and the positive electrode collector is high, the obtained lithium-ion battery has a high capacity and volume energy density, and the pass rate of the nail penetration test is high, which shows that the lithium-ion battery of this application can take into account the capacity, volume energy density and nail penetration safety performance.

[0157] The Dv50 of the first main material usually affects the capacity, volume energy density and nail penetration safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-4 to 1-9 that when the Dv50 of the first main material is within the scope of this application, the cohesion of the first coating is high, the adhesion between the first coating and the positive electrode collector is high, the obtained lithium-ion battery capacity and volume energy density are high, and the nail penetration test pass rate is high, which shows that the lithium-ion battery of this application can take into account the capacity, volume energy density and nail penetration safety performance.

[0158] The mass percentage of the first component usually affects the capacity, volume energy density and nail penetration safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-10 to 1-14 that when the mass percentage of the first component is within the range of this application, the cohesion of the first coating is high, the adhesion between the first coating and the positive electrode collector is high, the obtained lithium-ion battery capacity and volume energy density are high, and the nail penetration test pass rate is high, which shows that the lithium-ion battery of this application can take into account the capacity, volume energy density and nail penetration safety performance.

[0159] The mass percentage of carbon, nitrogen and oxygen usually affects the capacity, volume energy density and nail penetration safety performance of lithium-ion batteries. It can be seen from Examples 1-1, 1-15 to 1-23 that when the mass percentage of carbon, nitrogen and oxygen is within the range of this application, the cohesion of the first coating is high, the adhesion between the first coating and the positive electrode collector is high, the obtained lithium-ion battery capacity and volume energy density are high, and the nail penetration test pass rate is high, which shows that the lithium-ion battery of this application can take into account the capacity, volume energy density and nail penetration safety performance.

[0160] The thickness of the first coating layer usually affects the capacity, volume energy density and nail penetration safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-24 to 1-29 that when the thickness of the first coating layer is within the range of this application, the cohesion of the first coating layer is high, the bonding force between the first coating layer and the positive electrode current collector is high, the obtained lithium-ion battery capacity and volume energy density are high, and the nail penetration test pass rate is high, which shows that the lithium-ion battery of this application can take into account the capacity, volume energy density and nail penetration safety performance.

[0161] It can be seen from Examples 1-1 and 2-1 to 2-12 that when the mass percentage of the first main material, the type of lithium supplement material, the mass percentage of the first conductive agent, the type and mass percentage of the first binder, and the secondary particle size of the first conductive agent are within the scope of the present application, the obtained lithium-ion battery capacity and volume energy density are higher, and the pass rate of the nail penetration test is higher, which indicates that the capacity, volume energy density and nail penetration safety performance of the lithium-ion battery of the present application are improved.

[0162] from Figure 4 It can be seen that in the scanning electron microscope image of the cross section of the positive electrode sheet, the secondary particles of the first conductive agent cannot be observed, indicating that the particle size of the secondary particles of the first conductive agent is less than 50 nm, so that the first conductive agent has good dispersion in the first coating.

[0163] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

[0164] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0165] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

Claims

1. An electrochemical device, comprising a positive electrode sheet, the positive electrode sheet comprising a positive current collector, a first coating and a positive electrode material layer, the first coating being disposed on a surface of the positive current collector, the positive electrode material layer being disposed on a surface of the first coating away from the positive current collector, the first coating comprising a first main material and a first binder, the first main material comprising a lithium supplement material, the lithium supplement material comprising at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium orthosilicate or lithium ferrite; the infrared spectrum of the first coating is at 3200cm -1 Up to 3400cm -1 There are characteristic peaks between them.

2. The electrochemical device according to claim 1, wherein: At least part of the surface of the lithium-supplementing material has a first component, and the first component includes carbon, nitrogen and oxygen. Based on the mass of the first component, the mass percentage of the carbon element is 63.5% to 73.8%, the mass percentage of the nitrogen element is 7.6% to 17.9%, and the mass percentage of the oxygen element is 12% to 24.5%.

3. The electrochemical device according to claim 2, wherein: Based on the mass of the first component, the mass percentage of the carbon element is 66.25% to 70.1%, the mass percentage of the nitrogen element is 7.8% to 17.5%, and the mass percentage of the oxygen element is 12.4% to 22.3%.

4. The electrochemical device according to claim 2, wherein: Based on the mass of the first main material, the mass percentage of the first component is 2% to 10%.

5. The electrochemical device according to claim 1, wherein The Dv50 of the first main material is 50nm to 200nm.

6. The electrochemical device according to claim 5, wherein: The Dv50 of the first main material is 100nm to 150nm.

7. The electrochemical device according to claim 1, wherein: Based on the mass of the first coating layer, the mass percentage of the first main material is 84.5% to 94.8%.

8. The electrochemical device according to claim 1, wherein The sphericity of the first main material is 0.705 to 0.

874.

9. The electrochemical device according to claim 1, wherein: The first binder includes a water-soluble polymer metal salt; based on the mass of the first coating layer, the mass percentage of the first binder is 5.2% to 15.5%.

10. The electrochemical device according to claim 9, wherein: The metal element in the water-soluble polymer metal salt includes at least one of lithium, sodium, potassium, rubidium, cesium, francium, beryllium, barium, strontium, calcium or magnesium; the polymer in the water-soluble polymer metal salt includes at least one of polyacrylic acid, carboxymethyl cellulose, polyacrylonitrile or styrene butadiene.

11. The electrochemical device according to claim 10, wherein: The water-soluble polymer metal salt includes at least one of sodium polyacrylate, lithium polyacrylate, potassium polyacrylate, calcium polyacrylate, magnesium polyacrylate, lithium carboxymethyl cellulose or sodium carboxymethyl cellulose.

12. The electrochemical device according to any one of claims 1 to 11, wherein: The first coating also includes a first conductive agent, which includes at least one of conductive carbon black, activated carbon, carbon nanotubes or carbon nanofibers; based on the mass of the first coating, the mass percentage of the first conductive agent is 0.2% to 0.5%.

13. The electrochemical device according to claim 12, wherein: The particle size of the secondary particles of the first conductive agent is less than 50 nm.

14. The electrochemical device according to any one of claims 1 to 11, wherein: The thickness of the first coating layer is 0.2 μm to 2 μm.

15. The electrochemical device according to any one of claims 1 to 11, wherein: The electrochemical device satisfies at least one of the following conditions: (1) The thickness of the first coating is 0.5 μm to 2 μm; (2) The bonding force between the first coating layer and the positive electrode current collector is F1, 500 N / m≤F1≤900 N / m; (3) The cohesive force of the first coating is F2, 1400 N / m ≤ F2 ≤ 2500 N / m; (4) The membrane resistance of the positive electrode plate is 0.5Ω to 5Ω.

16. An electronic device comprising the electrochemical device according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Positive electrode slurry composition, and positive electrode plate, secondary battery, battery module, battery pack and electric device comprising same

    CN116848672A

  • Preparation and application of full-decomposition type positive electrode pre-lithiation agent

    CN117096469A

  • Pole piece preparation method, positive plate, electrochemical device and electronic equipment

    CN118588881A

  • Positive electrode plate, secondary battery, and electric apparatus

    EP4421898A1

Cited By

  • Electrochemical device and electronic device

    WO2026149192A1